Learning new words: Memory reactivation as a mechanism for strengthening and updating a novel word´s meaning - Laurino, Julieta (2020)
In the present study we explored the post-learning changes in a novel word’s definition using a cue-induced memory reactivation. Native speakers of Spanish (N=373) learned low-frequency words with their corresponding definitions. The following day, reactivated groups were exposed to a reminder and provided a subjective assessment of reactivation for each word, while control groups did not receive a reactivation. Study A demonstrated that memory reactivation enhances both explicit recall and semantic integration of new meanings. Study B investigated the effect of memory reactivation in the modification of the new meanings, through three different experiments. Results show an improvement of the updated definitions according to each word´s reactivation strength. In addition, congruence with previous knowledge was suggested to be a boundary condition, while consolidation time had a positive modulatory effect. Our findings call attention to reactivation as a factor allowing for malleability as well as persistence of long-term memories for words.